IMPROVED ALGORITHM FOR CALCULATING COMPLEX NON-EQUIPOTENTIAL GROUNDING DEVICES OF ELECTRICAL INSTALLATIONS TAKING INTO ACCOUNT CONDUCTIVITY OF NATURAL GROUNDINGS - K. A. Starkov (National Technical University "Kharkiv Polytechnic Institute", 2017)
Purpose. The method of natural concentrated groundings substitution by the set of electrodes taking them into account in the algorithm of electric characteristics calculation for complicated grounding connections of electric installation is offered. An equivalent model as a set of linear electrodes is chosen in accordance with two criteria: leakage resistance and potentials on the ground surface. Methodology. We have applied induced potential method and methods for computing branched electrical circuits with distributed parameters. Results. We have obtained the algorithm for calculating complex non-equipotential grounding connections, which makes it possible to obtain refined values of the potential distribution in the electric stations and substations with outdoor switchgear. Originality. For the first time, we have taking into account the conductivity of natural concentrated grounds by a set of vertical and horizontal electrodes based on equivalent electrical characteristics applied to a two-layer ground. Practical value. The using of the proposed calculation algorithm in the electric grids of JSC «Kharkivoblenergo» made it possible to determine the values of the potential distribution at short circuit in electrical substation taking into account the influence of the conductivity of natural concentrated groundings.